HUBUNGAN LAMA MENDERITA DAN KOMPLIKASI DENGAN KUALITAS HIDUP WANITA PENDERITA DIABETES MELLITUS TIPE II DI RS MITRA MEDIKA TAHUN 2022 - Nila Sari (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
According to the World Health Organization (WHO) in 2010 reported that 60% of the causes of death of all ages in the world are due to Non-Communicable Diseases (NCDs). Diabetes Mellitus is ranked 6th as the cause of death. Data obtained at the Binjai Army Hospital suffering from type II diabetes mellitus in 2022 there were 430 cases. The purpose of the study is to determine the relationship between long suffering and complications with the Quality of Life of Women With Type II Diabetes Mellitus at binjai Army Hospital in 2022". This study is observational analytic with a Cross Sectional design where the way data is collected at once at the same time until the number of samples is met as many as 120 people. Data were analyzed using simple logistic regression and multiple logistic regression tests. From the results of the bivariate analysis obtained for a long time suffering there was a significant influence on the quality of life of women with type II diabetes mellitus, where in obtaining an OR value of 2.688 with 95% CI: 1.226 – 5.895, showed that respondents who suffered from ≥ 5 years 2.688 times greater had a poor quality of life compared to respondents who suffered from < 5 years. Based on complications, obtained a p value > 0.05 meaning that it did not have a significant influence between complications with the quality of life of women with type II DM. It is recommended to health workers to intensify health promotion activities, socialization and provide education about a healthy lifestyle including regulating a healthy diet, controlling blood sugar levels and carrying out sufficient activities to neutralize fat levels and blood sugar levels in the body.